2010
DOI: 10.1203/pdr.0b013e3181e1cfce
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoiesis in Regenerated Bone Marrow Within Hydroxyapatite Scaffold

Abstract: ABSTRACT:We examined whether regenerated bone marrow (BM) with BM-derived stromal cells (BMSCs) on hydroxyapatite (HA) scaffolds can reconstitute the functional niche. Ly5.2 BMSCs on HA scaffolds were implanted s.c. onto the backs of Ly5.2 recipient mice. Lineage negative Ly5.1 BM cells expressing luciferase (luc) were i.v. administered into the recipient mice. Eight weeks after primary transplantation, secondary implantation was performed; the scaffolds removed from the first recipient mice were s.c. implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…We not only observed that CD34 ϩ hematopoietic progenitor cells themselves can engraft, but that hematopoietic cells of distinct lineages are also generated. Consistent with recent murine data, 33 this indicates that the human BM microenvironment engineered in our scaffolds serves as a functional hematopoietic niche and supports the engraftment and growth of hematopoietic (precursor) cells.…”
Section: Discussionsupporting
confidence: 91%
“…We not only observed that CD34 ϩ hematopoietic progenitor cells themselves can engraft, but that hematopoietic cells of distinct lineages are also generated. Consistent with recent murine data, 33 this indicates that the human BM microenvironment engineered in our scaffolds serves as a functional hematopoietic niche and supports the engraftment and growth of hematopoietic (precursor) cells.…”
Section: Discussionsupporting
confidence: 91%
“…The applied biomaterials can be roughly subdivided according to the used materials and their architecture. Besides some inorganic biomaterials such as hydroxyapatite 37 , mostly hydrogels are used to mimic the HSC niche. These hydrogels are produced from natural (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown host-cell-mediated hematopoiesis in ectopic bone tissues (17)(18)(19)(20)(21)(22)(23)(24)(25). These approaches include implantation of osteoinductive materials like demineralized bone powder (20), bone shafts (18), cell-laden synthetic or biological biomaterials (19,(21)(22)(23)(24)(25)(26) in ectopic sites such as s.c. tissue, small bowel mesentery, or subrenal capsule.…”
mentioning
confidence: 99%
“…These approaches include implantation of osteoinductive materials like demineralized bone powder (20), bone shafts (18), cell-laden synthetic or biological biomaterials (19,(21)(22)(23)(24)(25)(26) in ectopic sites such as s.c. tissue, small bowel mesentery, or subrenal capsule. These studies have demonstrated that engineered ectopic bone tissues can recruit host hematopoietic cells (17)(18)(19)(20)(21)(22)26) or attract i.v.-administered donor hematopoietic progenitor cells to reconstitute the BM environment (23)(24)(25)27). …”
mentioning
confidence: 99%